A Computational Approach to Elucidate the Interactions of Chemicals From Artemisia annua Targeted Toward SARS-CoV-2 Main Protease Inhibition for COVID-19 Treatment - Johnson, Titilayo Omolara; Adegboyega, Abayomi Emmanuel; Ojo, Oluwafemi Adeleke; Yusuf, Amina Jega; Iwaloye, Opeyemi; Ugwah-Oguejiofor, Chinenye Jane; Asomadu, Rita Onyekachukwu; Chukwuma, Ifeoma Felicia; Ejembi, Stephen Adakole; Ugwuja, Emmanuel Ike; Alotaibi, Saqer S.; Albogami, Sarah M.; et al. (Frontiers in Medicine, 2022)
The inhibitory potential of Artemisia annua, a well-known antimalarial herb, against several viruses including the coronavirus is increasingly gaining recognition. The plant extract has shown significant activity against both the Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV) and the novel SARS-CoV-2, that is currently ravaging the world. It is therefore necessary to evaluate individual chemicals of the plant for inhibitory potentials against SARS-CoV-2, for the purpose of designing drugs for the treatment of COVID-19. In this study, we employed computational techniques comprising of molecular docking, binding free energy calculations, pharmacophore modelling, induced-fit docking, molecular dynamics simulation as well as ADMET predictions, to identify potential inhibitors of the SARS-CoV-2 main protease (Mpro) from 168 bioactive compounds of Artemisia annua. Rhamnocitrin, isokaempferide, kaempferol, quercimeritrin, apigenin, penduletin, isoquercitrin, astragalin, luteolin-7-glucoside and isorhamnetin were ranked highest; with docking scores ranging from -7.84 to -7.15 kcal/mol compared with -6.59 kcal/mol demonstrated by the standard ligand. Rhamnocitrin, isokaempferide and kaempferol, like the standard ligand interacted with important active site amino acid residues like HIS 41, CYS 145, ASN 142, and GLU 166, among others. Rhamnocitrin demonstrated good stability in the active site of the protein as there were no significant conformational changes during the simulation process. These compounds also possess acceptable druglike properties and safety profile. Hence, they could be considered for experimental studies and further development into drugs against COVID-19.